2014
DOI: 10.1039/c3tb21801e
|View full text |Cite
|
Sign up to set email alerts
|

A multifunctional perylenediimide derivative (DTPDI) can be used as a recyclable specific Hg2+ ion sensor and an efficient DNA delivery carrier

Abstract: A multifunctional perylenediimide derivative (DTPDI) can be used as a recyclable specific Hg2+ ion sensor and an efficient DNA delivery carrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 41 publications
(16 reference statements)
0
53
0
Order By: Relevance
“…[108][109][110][111][112][113][114][115] APHPs have been used in drug loading and release applications, as evidenced by the increasing number of publications in recent years. [108][109][110][111][112][113][114][115] APHPs have been used in drug loading and release applications, as evidenced by the increasing number of publications in recent years.…”
Section: Drug Loading and Releasementioning
confidence: 99%
“…[108][109][110][111][112][113][114][115] APHPs have been used in drug loading and release applications, as evidenced by the increasing number of publications in recent years. [108][109][110][111][112][113][114][115] APHPs have been used in drug loading and release applications, as evidenced by the increasing number of publications in recent years.…”
Section: Drug Loading and Releasementioning
confidence: 99%
“…For example, change of the substituent in salicylaldehyde salicylhydrazone probe lead to tunable fluorescence sensing of Mg 2+ and Zn 2+ Xu et al, 2014;hoi et al, 2014;ar n-ern ndez et al, 2014;Wu et al, 2013) [11]. Different sensitivity for Mg 2+ was observed with coumarin-based fluorophore by modifying the substituent Sen et al, 2012) [12].…”
Section: Introductionmentioning
confidence: 99%
“…Imidazole based juloidine chemoprobe showed selective sensing of different metal ions in different solvents Hornung et al, 2008) [13]. With the intent of developing new optical probes based on Schiff base ligand for selective sensing of metal ions, fluorescence turn-on probes have been described, wherein the mechanism of sensing has been largely attributed to internal charge transfer (ICT) (Karton-Lifshin et al, 2012;Delcamp et al, 2013;Goswami et al, 2013;Rihn et al, 2012) [14], chelation-enhanced fluorescence (CHEF) (Albers et al, 2006;Sreenath et al, 2011;Zhou et al, 2012;Tan et al, 2015) [15], photo-induced electron transfer (PET) (Liu et al, 2014;Baek et al, 2012;Masanta et al, 2011;Chen et al, 2015) [16] or fluorescent resonance energy transfer (FRET) Sapsford et al, 2006;Qin et al, 2015;Yuan et al, 2015) [17]. Among them, chelation-enhanced fluorescence probe is a current thrust in the active research field interesting.…”
Section: Introductionmentioning
confidence: 99%
“…Yin et al reported a selective fluorescent chemosensor based on ACQ dye 3 for recyclable detection with high sensitivity (Figure 3) [18]. With the addition of 20 mM of Hg…”
Section: Sensing Mechanism Of Synthetic Dyes For Environmental Applicmentioning
confidence: 99%